2019
DOI: 10.1080/15389588.2019.1602770
|View full text |Cite
|
Sign up to set email alerts
|

Roadside design assessment in an urban, low-density environment in the Gulf Cooperation Council region

Abstract: Objectives: Proper roadside design is crucial in order to mitigate the consequences associated with single-vehicle runoff road (SVROR) crashes. However, the Gulf Cooperation Council (GCC) region lacks in-depth, detailed information on its roadside design status. Hence, there is a need for an in-service evaluation of roadside design in the GCC region. The objective of this study is to assess the existing roadside design in a medium-sized, low-density city in the United Arab Emirates (UAE). Methods: A multiyear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…If, and only if, none of these design priorities can be implemented, shielding should be considered. Unfortunately, research has shown that roadside design compliance has been lacking [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If, and only if, none of these design priorities can be implemented, shielding should be considered. Unfortunately, research has shown that roadside design compliance has been lacking [7].…”
Section: Resultsmentioning
confidence: 99%
“…SVROR, fixed-object crashes account for a large portion of all SVROR-injury crashes [1][2][3][4][5][6]. Fixed objects such as poles, trees, and barriers have been found to be the most harmful object struck by errant vehicles [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows that almost 22% of all SVROR-injury crashes involved severe injuries while a staggering 89.5% (see number in bold) occurred at locations found to be non-compliant. This indicates that meeting roadside design compliance may be slightly more challenging in a dense, urban area as compared to areas that are not densely populated [33]. This may be attributed to more limited right-of-way (ROW) availability in densely populated areas and may be an indication of the need for research related to the identification of a more practical, minimum-recommended-CZ-distance policy for urban areas.…”
Section: Data Tabulationmentioning
confidence: 99%